2019
DOI: 10.1111/jsr.12878
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic dynamics during sleep are lost in patients with TIA and stroke

Abstract: Ischaemic stroke is accompanied by important alterations of cardiac autonomic control, which have an impact on stroke outcome. In sleep, cardiac autonomic control oscillates with a predominant sympathetic modulation during REM sleep. We aimed to assess cardiac autonomic control in different sleep stages in patients with ischaemic stroke. Forty‐five patients enrolled in the prospective, multicentre SAS‐CARE study but without significant sleep‐disordered breathing (apnea–hypopnea index < 15/hr) and without atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…stroke Tobaldini et al reported predominant vagal modulation and decreased sympathetic modulation across all sleep stages[33]. Based on our observation of RR interval variations as a demonstration of sympathovagal balance, the most notable difference occurs in non-REM sleep…”
supporting
confidence: 57%
See 1 more Smart Citation
“…stroke Tobaldini et al reported predominant vagal modulation and decreased sympathetic modulation across all sleep stages[33]. Based on our observation of RR interval variations as a demonstration of sympathovagal balance, the most notable difference occurs in non-REM sleep…”
supporting
confidence: 57%
“…Brunetti et al observed that compared to controls, acute stroke patients have a predominant parasympathetic tone during wake and REM sleep accompanied by a reduction of sympathetic tone in REM and parasympathetic tone during N3 [ 32 ]. Tobaldini et al reported predominant vagal modulation and decreased sympathetic modulation across all sleep stages [ 33 ]. Based on our observation of RR interval variations as a demonstration of sympathovagal balance, the most notable difference occurs in non-REM sleep specifically in N2 and N3 sleep between OSA patients with and without stroke history.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that autonomic dysfunction in stroke patients could be prolonged for up to four years after the ictus and is manifested as reduced parasympathetic activity 48,49 . Also, recent studies showed that abnormal time-domain (SDNN, RMSS), frequency-domain (LF, HF, spectral power in the very low-frequency range -VLF) parameters and nonlinear entropy parameters (DFA, ApEN) are predictors for stroke severity, functional outcome, and mortality 50 . Less variability, loss of parasympathetic tonus and HRV parameters altered during the sleep cycle are associated with worse prognosis 50,51 .…”
Section: Chronic Phasementioning
confidence: 99%
“…Also, recent studies showed that abnormal time-domain (SDNN, RMSS), frequency-domain (LF, HF, spectral power in the very low-frequency range -VLF) parameters and nonlinear entropy parameters (DFA, ApEN) are predictors for stroke severity, functional outcome, and mortality 50 . Less variability, loss of parasympathetic tonus and HRV parameters altered during the sleep cycle are associated with worse prognosis 50,51 . However, HRV parameters as biomarkers for stroke still require the integration of linear and nonlinear methods to expand the risk modeling and improve its predictive value.…”
Section: Chronic Phasementioning
confidence: 99%
“…Additionally, there is no universal recommendation which HRV parameters are best for examining the autonomic nervous system. Although researchers have been traditionally using linear time-domain or frequency-domain parameters ( Sethi et al, 2016 ; Chidambaram et al, 2017 ), more recently, researchers have used non-linear parameters such as approximate entropy, multiscale entropy, detrended fluctuations, and fractal dimensions (FDs) ( Tobaldini et al, 2019a ; Tobaldini et al, 2019b ; He et al, 2019 ) to provide additional or alternative insights into the investigated physiological states. Furthermore, the exact mechanism responsible for poor outcomes in patients with stroke showing reduced HRV remains unclear.…”
Section: Introductionmentioning
confidence: 99%